Habitual dietary nitrate intake in highly trained athletes - Jonvik, K. L.; Nyakayiru, J.; van Dijk, J.-W.; Wardenaar, F. C.; van Loon, L. J. C.; Verdijk, L. B. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Although beetroot juice, as a nitrate carrier, is a popular ergogenic supplement among athletes, nitrate is consumed through the regular diet as well. We aimed to assess the habitual dietary nitrate intake and identify the main contributing food sources in a large group of highly trained athletes. Dutch highly trained athletes (226 women and 327 men) completed 2-4 web-based 24-hr dietary recalls and questionnaires within a 2- to 4-week period. The nitrate content of food products and food groups was determined systematically based on values found in regulatory reports and scientific literature. These were then used to calculate each athlete`s dietary nitrate intake from the web-based recalls. The median[IQR] habitual nitrate intake was 106[75-170] mg/d (range 19-525 mg/d). Nitrate intake correlated with energy intake (p = 0.28, p < .001), and strongly correlated with vegetable intake (p = 0.78, p < .001). In accordance, most of the dietary nitrate was consumed through vegetables, potatoes and fruit, accounting for 74% of total nitrate intake, with lettuce and spinach contributing most. When corrected for energy intake, nitrate intake was substantially higher in female vs male athletes (12.8[9.2-20.0] vs 9.4[6.2-13.8] mg/MJ; p < .001). This difference was attributed to the higher vegetable intake in female vs male athletes (150[88-236] vs 114[61-183] g/d; p < .001). In conclusion, median daily intake of dietary nitrate in highly trained athletes was 106 mg, with large interindividual variation. Dietary nitrate intake was strongly associated with the intake of vegetables. Increasing the intake of nitrate-rich vegetables in the diet might serve as an alternative strategy for nitrate supplementation.